Program Pemberdayaan Terhadap Wanita Rawan Sosial Ekonomi Di Desa Margamulya - Ismet Firdaus; Adinda Destria; Winda Rahmadini; M Alvi Wijaya; M Rizky Akmal; Febriyanti (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Economic problems and poverty are phenomena that cannot be separated from the life of society in every country, as both are interrelated. One of the causes of poverty is the persistent culture of gender discrimination in employment, particularly affecting women. This has also led to an increase in the number of economically vulnerable women (WRSE) in Indonesia. The Indonesian Ministry of Administrative and Bureaucratic Reform (KemenPANRB, 2023) defines WRSE as women of productive age (18-59 years) who face economic difficulties, have limited education, experience changes in family status or become widows due to the death of their husbands, and face health challenges. WRSE are required to manage their households while also earning a livelihood to support their families. Empowerment is necessary because the majority of these women lack employment or skills. Based on the data collected, the village of Margamulya has the highest WRSE figures in RW 02 and RW 19. In efforts to address and minimize WRSE, this research aims to provide recommendations for improving their conditions. This is a descriptive qualitative study, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted using triangulation techniques to enhance the validity of the findings.